2021
DOI: 10.3390/ani11051202
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Albumin by Preovulatory Oviductal Fluid in Swim-Up Sperm Preparation Method Modifies Boar Sperm Parameters and Improves In Vitro Penetration of Oocytes

Abstract: More suitable and efficient methods to protect gametes from external harmful effects during in vitro handling can be achieved by adding preovulatory porcine oviductal fluid (pOF) to in vitro culture media. The objective of this study was to assess the swim-up procedure’s suitability as a sperm selection method using a medium supplemented with 1mg/mL BSA, 1% preovulatory pOF (v/v), 1% v/v pOF plus 1mg/mL BSA, and 5mg/mL BSA. After selection, various sperm parameters were studied, such as sperm recovery rate, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In sperm porcine similar results regarding effect of swim-up on decreasing the bent tails was reported (Navarro-Serna et al, 2021). Swim-up selects a high proportion of sperm with normal morphology (Rodríguez-Martinez et al, 1997), based on migration of progressively motile sperm (Hoogewijs et al, 20012).…”
Section: Discussionmentioning
confidence: 77%
“…In sperm porcine similar results regarding effect of swim-up on decreasing the bent tails was reported (Navarro-Serna et al, 2021). Swim-up selects a high proportion of sperm with normal morphology (Rodríguez-Martinez et al, 1997), based on migration of progressively motile sperm (Hoogewijs et al, 20012).…”
Section: Discussionmentioning
confidence: 77%
“…In vitro matured oocytes were washed in TALP medium [47] supplemented with 1 mM sodium pyruvate, 0.3% BSA, and 50 µg/mL gentamycin (IVF-TALP), and transferred in groups of 50-55 oocytes to each well containing 250 µL IVF-TALP medium. Oocytes were inseminated with frozen-thawed ejaculated spermatozoa from a fertile boar that had been selected by a swim-up procedure [48]. One 0.25 mL-straw was thawed in a water bath (30 s, 38 • C) and semen diluted in 2 mL NaturARTsPIG sperm swim-up media (Embryocloud, Murcia, Spain) at 38 • C. Sperm selection was performed by adding 1 mL sperm swim-up media in a conical tube and 1 mL thawed-diluted sperm to the bottom of the tube.…”
Section: In Vitro Fertilization (Ivf)mentioning
confidence: 99%
“…(García-Álvarez et al, 2015;García-Herreros and Leal, 2014;Lukoseviciute et al, 2004;Parrish et al, 1988). There is also an observable trend where the consideration of the use of capacitation inducers leads to recreating the physiological environment of the female genital tract (Chaves et al, 2021), using substances that have been identified to modulate sperm capacitation in vivo such as oviductal fluid (OF) (Navarro-Serna et al, 2021), creatine (Umehara et al, 2018), and the involvement of hormones (estrogen and progesterone) (García-Álvarez et al, 2015). Essentially, the primary goal of in vitro capacitation process is to produce capacitated spermatozoa effectively (Chaves et al, 2021) and efficiently, with intact acrosome membrane, hyperactive motility, and the distribution of protein complexes in the apical ridge of spermatozoa associated with zona-binding and zona-induced acrosome reaction (Gadella and Luna, 2014), so that the direction of spermatozoa movement towards oocyte is not disturbed (proven by high sperm bound to oocyte/ZP) (Boerke et al, 2013).…”
Section: Flaws and Improvementsmentioning
confidence: 99%